Moving to Linux® : Kiss the Blue Screen of Death Goodbye! Second Edition - Gagné, Marcel (Addison-Wesley Professional, 2005)
Praise for Marcel Gagné's Moving to Linux: Kiss the Blue Screen of Death Goodbye! "This is kind of a funny book for me to be recommending to readers of a Windows newsletter, but a lot of people ask me about this topic, so here goes. Author Marcel Gagné is a columnist for Linux Journal , and in Moving to Linux he's prepared a step-by-step guide to converting a Windows PC to Linux--or just trying it! The book includes a bootable CD with a version of Linux that you can poke around in without touching or changing anything about your Windows installation. If your boss is asking, 'What's with this Linux stuff?', moving to Linux is a great way to show that you know what you're talking about." --Brian Livingston, Editor, WindowsSecrets.com "Pros: Too many to list in the available space. We liked the book from the very first page right through to the end. Gagné has done a solid job of exposing Linux and all its components in a way that is both inviting, useful, and easy to understand . . . We really liked this book--highly recommended." --Howard Carson, Kickstart News, www.kickstartnews.com "Marcel walks the user through each technique in a very chatty and comfortable style. In fact, when I put the book down, I had a momentary impression that I'd just finished watching a good cooking show with an entertaining chef. (Australian readers may understand if I say that it felt like having just watched Ian Parmenter do an episode of 'Consuming Passions.')" --Jenn Vesperman, Linuxchix.org "Gagné's Moving to Linux is a straightforward exposition of just how a non-hacker PC user can get rid of 'The Blue Screen of Death'. If you have a friend, a co-worker, a significant other, or a relative who periodically screams, sighs, bursts into tears, or asks for help, here's the simple solution. It comes with a bootable CD of Knoppix, Klaus Knopper's variant of Debian." --Peter H. Salus, writing in ;login: The Usenix Magazine "This is a book aimed not at you, dear developer/techie/guru, but at your friends, acquaintances, and family who are lowly users of Windows. Yes, such people do exist even in the tightest of families. Fear not, however, because salvation is at hand should any of them decide that this Linux thing might be worth investigating. No longer will you be faced with the unenviable task of walking them through the process of switching OS. Moving to Linux: Kiss the Blue Screen of Death Goodbye! is a big, bold, and friendly guide to help them along. The emphasis i...